2-[4-Acetyl-5-(biphenyl-4-yl)-4,5-dihydro-1,3,4-oxadiazol-2-yl]phenyl acetate - Yehye, Wagee A. (International Union of Crystallography, 2010)
In the title molecule, C(24)H(20)N(2)O(4), the five-membered oxadiazole ring is nearly planar (r.m.s. deviation = 0.053 Å) and the phenyl ring of the biphenyl unit attached to it forms a dihedral angle of 73.2 (1)°; the other phenyl ring is close to coplanar with the oxadiazole ring [dihedral angle = 6.2 (2)°].